2006
DOI: 10.1158/0008-5472.can-05-3166
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Computational/Experimental Model of Tumor Invasion

Abstract: The intracellular and extracellular dynamics that govern tumor growth and invasiveness in vivo remain poorly understood. Cell genotype and phenotype, and nutrient, oxygen, and growth factor concentrations are key variables. In previous work, using a reaction-diffusion mathematical model based on variables that directly describe tumor cell cycle and biology, we formulated the hypothesis that tumor morphology is determined by the competition between heterogeneous cell proliferation caused by spatial diffusion gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
275
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 273 publications
(317 citation statements)
references
References 50 publications
(60 reference statements)
39
275
0
3
Order By: Relevance
“…By considering a characteristic diffusion constant for nutrient D n ≈ 10 −5 cm 2 /s and a nutrient consumption rate υ U ≈ 1 min −1 (the latter from the observation that brain cells run out of glucose and die on that time scale), a characteristic nutrient diffusion length L ≈ 200 − 300µm is obtained. This is consistent with the observed thickness of the viable rim of cells in tumor spheroids in vitro [2,74]. For the simulation illustrated in Fig.…”
Section: Microphysical Parameters For Malignant Gliomasupporting
confidence: 87%
See 2 more Smart Citations
“…By considering a characteristic diffusion constant for nutrient D n ≈ 10 −5 cm 2 /s and a nutrient consumption rate υ U ≈ 1 min −1 (the latter from the observation that brain cells run out of glucose and die on that time scale), a characteristic nutrient diffusion length L ≈ 200 − 300µm is obtained. This is consistent with the observed thickness of the viable rim of cells in tumor spheroids in vitro [2,74]. For the simulation illustrated in Fig.…”
Section: Microphysical Parameters For Malignant Gliomasupporting
confidence: 87%
“…In vivo, for example, malignant glioma (brain tumor), apoptosis is probably negligible (λ A = 0) since mutated clones after the initial selection has occurred are typically characterized by suppression of the p53 pathway and enhanced proliferation [137], and even normal glial cells are immortal. From experiments [74] on growth of glioblastoma cell lines (the most malignant and proliferative brain tumors) as multicellular millimeter-size spheroids in vitro, it was observed that typically mitosis rate λ M ≈ 0.3 day −1 , that rate of volume loss in the necrotic core is comparable or less than the rate of volume gain from mitosis, hence the choice λ N = 0.25, and finally that minimum nutrient concentration for cell viability is a small fraction of outer uniform concentration in growth medium [74], hence the choice of a value for n N 1 (although the value of this parameter may be affected by the difficulty of reproducing the in vivo conditions in vitro). Dimensionless nutrient concentration in the blood is chosen as n C = 1, i.e., in equilibrium with the concentration in the undisturbed tissue environment.…”
Section: Microphysical Parameters For Malignant Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…Most early work in this area involved the incorporation of adhesion via a surface tension on the tumour boundary (Byrne & Chaplain 1996;Chaplain 1996;Cristini et al 2003;Frieboes et al 2006Frieboes et al , 2007Friedman 2007;. This representation of adhesion is indirect: there is no explicit modelling of cell-cell or cell-matrix contact.…”
Section: Modelling Adhesion In Invasion Processesmentioning
confidence: 99%
“…Indeed, some studies have demonstrated that antiangiogenic therapy may interrupt the delivery of chemotherapeutic drugs to tumors (5) and diminish the effects of radiation therapy (6). In fact, computer simulations suggest that conventional treatment, including antiangiogenic therapies, may trigger spatial heterogeneity (e.g., local hypoxia), thus causing invasive instability (7) and selecting for more malignant cells with increased metastatic potential (8). Unfortunately, some cancer cells may survive in this abnormal microenvironment and regrow to recurrent disease or become the origin of metastatic seed.…”
mentioning
confidence: 99%